ANALISIS PERFORMA PROTOTIPE SISTEM PEMBANGKIT DAYA LISTRIK TERINTEGRASI PADA RODA KENDARAAN LISTRIK - Luthfi, Muhammad; Sifa, Agus; Fajri, Ade Ruli Nurul; Alfiansyah, Agil; Muhammad Luthfi (Jurnal Rekayasa Mesin, 2024)
The increasing use of electric bicycles and motorcycles in Indonesia has opened up significant opportunities for advancements in this type of vehicle, including the utilization of wheel rotation during operation. This research aims to evaluate the performance of a prototype electric power generation system directly installed within the wheels of electric bicycles or motorcycles. Quantitative research data were collected using experimental methods by measuring voltage, electric current, and battery charging time derived from the generated current under varying wheel rotation speeds and the number of stator coil poles. From the system testing results, the highest average voltage and current, along with the shortest battery charging time, which were 11.64 V, 2.29 A, and 20 minutes, respectively were achieved under conditions with the maximum number of stator poles and the highest rotation speed of 12 stator poles and a rotational speed of 1119.8 rpm respectively, which was equivalent to a travel speed of 73.88 km/h. In addition, the effect of addition of poles to the generated electricity power is not as significant as the change of the wheel rotation speed.